Conceptual approach to developing quality measures for transgender patients - Adam J. Rose; Michael S. Dunbar; Jaclyn M. W. Hughto; Guneet K. Jasuja (BMC, 2021)
Abstract Background Valid and reliable quality measures can help catalyze improvements in health care. The care of transgender patients is ripe for quality measurement, as there is increasing awareness of the increasing prevalence of this population and the urgency of improving the health care they receive. While best practices may not exist for some aspects of transgender health care, other aspects are characterized by well-developed and highly evidence-based recommendations. Our objective was to create a list of potential quality measures for transgender care. Methods and results In consultation with our advisory panel, which consisted of clinical and academic experts in transgender medicine, we selected eight prominent clinical practice guidelines of transgender health care for review. Our four team investigators carefully reviewed all eight clinical practice guidelines. Through the course of multiple consensus-building meetings, we iteratively refined items until we had agreed upon a list of forty potential quality measures, all of which met the criteria for quality measures set forth in the Center for Medicare and Medicaid Services Blueprint for developing quality measures. Conclusions This manuscript explains the origin of the quality measures we developed, and also provides a useful roadmap to any group hoping to develop quality measures for a field that has not previously had any.